1997
DOI: 10.3168/jds.s0022-0302(97)76184-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Bovine Lactoferrin Pepsin Hydrolysate on Murine Splenocytes and Peyer's Patch Cells

Abstract: The effects were examined of a pepsin hydrolysate of bovine lactoferrin on the proliferation of murine splenocytes. The hydrolysate enhanced [3H]thymidine uptake by splenocytes, but undigested bovine lactoferrin exerted an inhibitory effect. The hydrolysate had the ability to inhibit the blastogenesis that was induced by mitogens such as concanavalin A, phytohemagglutinin, and lipopolysaccharide; inhibition was similar to that with undigested lactoferrin. These results suggested that the hydrolysate contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 28 publications
3
28
1
4
Order By: Relevance
“…WPCs and PP fractions prepared from human and bovine milk have no effect on IgA production in murine Peyer's patch cell cultures (Shida et al, 1992), whereas GMP suppresses in vitro antibody production (plaque-forming cell, PFC) to sheep RBC in murine spleen cell cultures . A pepsic H of bLF containing LFc also significantly enhances immunoglobulin (IgM, IgG and IgA) production in cultured murine splenocytes and IgA production in Peyer's patch cells (Miyauchi et al, 1997).…”
Section: Modulation Of Antibody Productionmentioning
confidence: 98%
See 1 more Smart Citation
“…WPCs and PP fractions prepared from human and bovine milk have no effect on IgA production in murine Peyer's patch cell cultures (Shida et al, 1992), whereas GMP suppresses in vitro antibody production (plaque-forming cell, PFC) to sheep RBC in murine spleen cell cultures . A pepsic H of bLF containing LFc also significantly enhances immunoglobulin (IgM, IgG and IgA) production in cultured murine splenocytes and IgA production in Peyer's patch cells (Miyauchi et al, 1997).…”
Section: Modulation Of Antibody Productionmentioning
confidence: 98%
“…This study highlighted the importance of measuring LPS contamination in commercial whey protein products before studying their immunomodulatory properties. Miyauchi, Kaino, Shinoda, Fukuwatari, and Hayasawa (1997) showed that bovine lactoferrin (bLF) inhibits the proliferation of murine splenocytes while a peptic H of bLF promotes cell proliferation, especially in a B-cellenriched fraction as well as in Peyer's patch cells. They also showed that the peptic H inhibits the blastogenesis induced by mitogens (concanavalin A (ConA), phytohemagglutinin (PHA), LPS), as observed for intact bLF.…”
Section: Lymphocyte Activation and Proliferationmentioning
confidence: 99%
“…Notable among them are LF and LPO, which are basic proteins with respective pI values of 8-9 and 9.62 (Hahn, Schulz, Schaupp, & Jungbauer, 1998) and are bound to OPN in physiologically conditioned PBS with dissociation constants of 1.3 Â 10 À6 and 2.5 Â 10 À6 , respectively. LF functions as an antimicrobial agent for host defense and as a physiological regulator with respect to inflammatory and immune responses (Brock, 2002;Tomita, Wakabayashi, Yamauchi, Teraguchi, & Hayasawa, 2002;Miyauchi, Kaino, Shinoda, Fukuwatari, & Hayasawa, 1997), inhibiting complement activity (Kijlstra & Jeurissen, 1982), and activating NK cells, lymphokineactivated killer cells (Shau, Kim, & Golub, 1992), polymorphonuclear leukocytes and macrophages (Gahr, Speer, Damerau, & Sawatzki, 1991). LPO, a hemecontaining oxidation-reduction enzyme, is part of an antimicrobial system that converts thiocyanate to hydrothiocyanate which can kill both Gram-positive (Steele & Morrisons, 1969) and Gram-negative (Bjo¨rck, Rosen, Marshall, & Reiter, 1975) bacteria.…”
Section: Article In Pressmentioning
confidence: 99%
“…Zimecki et al (1991) observed that the humoral immune response against sheep red blood cells increases up to five times in mice treated with a single injected dose of human LF, stimulating the immune response leading to T cell differentiation. Miyauchi et al (1997) demonstrated that a pepsin LF hydrolysate activates murine B cells, enhancing Ig secretion by splenocytes and IgA production in Peyer's Patch cells.…”
Section: Discussionmentioning
confidence: 98%